Metal Catalysts in Olefin Polymerization - Guan, Zhibin (Springer, 2017)
Polyolefin is a major industry that is important for our economy and impacts every aspect of our lives. The discovery of new transition metal-based catalysts is one of the driving forces for the further advancement of this field. Whereas the classical heterogeneous Ziegler-Natta catalysts and homogeneous early transition metal metallocene catalysts remain the workhorses of the polyolefin industry, in roughly the last decade, tremendous progress has been made in developing non-metallocene-based olefin polymerization catalysts. Particularly, the discovery of late transition metal-based olefin polymerization catalysts heralds a new era for this field. These late transition metal complexes not only exhibit high activities rivaling their early metal counterparts, but more importantly they offer unique properties for polymer architectural control and copolymerization with polar olefins. In this book, the most recent major breakthroughs in the development of new olefin polymerization catalysts, including early metal metallocene and non-metallocene complexes and late transition metal complexes, are discussed by leading experts. The authors highlight the most important discoveries in catalysts and their applications in designing new polyolefin-based functional materials.